The coaching of the periphery : the working class as a monster in the society of spectacle - Ángela Martínez Fernández (Études romanes de Brno)
This article analyzes the current state of weakening suffered by the class analysis and the hypothetical "death" of the working class, that is, it starts from a contextual framework in which the working-class is put in doubt (Olin Wright 2018). Along with the discourses of the social space, culture also intervenes and reproduces this state of confusion, weakening and stigmatization through products that shape the working-class referent in different ideological directions. Thus, the cultural territory of the new millennium intervenes in the battles for the meaning of the working class and wields two possibilities: the revitalization of the working class referent or the negation and invisibilization in favor of other structures of thought that do not use the social class as an axis. In this second variant, considered hegemonic in recent decades, a specific current emerges that uses "monstrification" (Jaume Peris Blanes 2019) to associate the working class with the abject values of the monsters of fiction. In this way, cultural logics relate the working class with characteristics of the monstrous and reinforce demonizing imaginaries that serve to project prejudices towards the working class social strata. We use, as a paradigm of how this works, a cinematographic proposal (Las colinas tienen ojos 2006) and observe how its logics of monstrification are reproduced in Spain through reality television programs (Hermano mayor 2009). We wonder, then, to what extent the tools used by American horror cinema can be translated into the most popular makeover shows of the last decade (Mercè Oliva 2013), those in which the abject working class is the object of representation. The article traces, in short, the forms that culture uses to intervene in the procedures of weakening the working class.